(untitled) (UNED Research Journal, 2020)
Introduction: The fish Centropomus undecimalis ingests whole prey by swimming rapidly and extending its jaws. It is a non-violent predator that follows a predator-prey size relationship. Objective: To inform a case of predation of C. undecimalis, a disproportionally large prey. Methods: Freshly caught fish from El Carmen lagoon, Tabasco, Mexico, were examined. Results: a Gobionellus oceanicus that was 56% the length of its predator, was found inside a C. undecimalis; the prey was bent in the stomach of its predator and had a bite wound in the middle of its body. Conclusions: apparently, C. undecimalis caught the prey with a single bite and swallowed it by folding the body in half: prey length is not the only determinant of when a prey is successfully captured by this fish.